Thematic analysis of multiple sclerosis research by enhanced strategic diagram. (December 2022) - Shafin, Nazlahshaniza; Ismail, Che Aishah Nazariah; Mustafa, Mohd Zulkifli; Ghani, Nurhafizah; Ahmad, Asma Hayati; Othman, Zahiruddin; Wijaya, Adi; Zakaria, Rahimah
Recent interest in multiple sclerosis research warrants literature analysis to evaluate the current state of the discipline and new research domains. This bibliometric review summarised the research trends and analysed research areas in multiple sclerosis over the last decade. The documents containing the term 'multiple sclerosis' in the article title were retrieved from the Scopus database. We used Harzing's Publish or Perish and VOSviewer for citation analysis and data visualisation, respectively. We found a total of 18, 003 articles published in journals in the English language between 2012 and 2021. The emerging keywords identified utilising the enhanced strategic diagram were 'covid-19', 'teriflunomide', 'clinical trial', 'microglia', 'b cells', 'myelin', 'brain', 'white matter', 'functional connectivity', 'pain', 'employment', 'health-related quality of life', 'meta-analysis' and 'comorbidity'. This study demonstrates the tremendous growth of multiple sclerosis literature worldwide, which is expected to grow more than double during the next decade especially in the identified emerging topics.